RESPIRATORY EXERCISE MACHINES WITHIN COMPLEX MANAGEMENT OF ACUTE RESPIRATORY FAILURE OF VARIOUS GENESIS - A. V. VLАSENKO; А. G. KORYAKIN; E. P. RODIONOV; E. А. EVDOKIMOV (Вестник анестезиологии и реаниматологии, 2019)
.